Problem Confrontation of the FFS Farmers in Participating Farmer Field School Training Session - Roy, D; Farouque, MG; Rahman, MZ (Progressive Agriculture, 2014)
The study was conducted to identify and describe the problems of FFS farmers in participating FFS training sessions. Data and information were collected from 100 FFS farmers of selected three unions of Muktagacha Upazila of Mymensingh district in Bangladesh from 10 to 30 April, 2013. Among ten selected problems Inadequate trials and training materials got the highest score (PCI-176) while Biasness in trainee selection got the lowest score (PCI-48). The highest proportion of the FFS farmers (53%) had low problem in participating FFS training session, while 40% and 7% had medium and high problem, respectively. Findings indicate that a majority i.e. more than four fifth of the FFS farmers faced low to medium problems in participating FFS training sessions. The selected characteristics of the FFS farmers, such as year of schooling, farming experience, extension media contact, risk orientation and knowledge on soil and crop management showed significantly negative relationship with problem confrontation in participating FFS training sessions by the FFS farmers. Therefore, it can be mentioned that there is no significant problems associated with the FFS training sessions. So, necessary steps need to be taken to enhance the existing activities of FFS that could improve the sustainable crop production as well as the livelihood of the FFS farmers. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19179 Progress. Agric. 24(1&2): 273 - 280, 2013